Detection and control of transverse cracks on rotating machines - Leão, Leandro de Souza (2019)
In this dissertation, crack detection and crack control of rotating machinery are addressed. The objectives of this study involves building and validating a numerical model capable of simulating the dynamic behavior of a real rotating machine. Numerical and experimental results for crack detection based on the shaft vibration signals are obtained. Besides, numerical and experimental results from an active control method, capable of suppressing 2X and 3X super-harmonics are obtained, excited by the crack presence. The innovation of this thesis lays on the fact of merging crack detection and crack control techniques in one single study. It is worth mentioning that the subject of crack control is quite new in the literature. The rotor is modeled by the finite element (FE) method, considering Timoshenko beam elements with circular cross section and constant radius. The Mayes model is addressed for simulating the breathing behavior of a transverse crack in a progressive way. The linear fracture mechanics theory is applied to correlate the crack depth with the corresponding additional shaft flexibility. The so-called modal state observer (MSO) technique was chosen to verify the existence of a transverse crack on a rotating machine. Moreover, the PID active control technique was addressed to perform crack control, suppressing crack signatures over the rotor frequency spectrum. Both numerical and experimental results highlight the possibility of detecting the existence of a crack and also how to decrease its effects (through active control) of an operating rotating machine. In this way, inspections requiring full stop of the machine can be performed less often while keeping the rotating machine safety.